A GP Caregiver Needs Toolkit versus usual care in the management of the needs of caregivers of patients with advanced cancer: a randomised controlled trial - Mitchell, G.; Girgis, A.; Jiwa, Moyez; Sibbritt, D.; Burridge, L. (BioMed Central, 2010)
Background: Caring for a person with progressive cancer creates challenges for caregivers. However the needs of caregivers are often not assessed or recognised by health care providers. Research is also lacking in this area, with little knowledge relating to effective strategies to address the specific needs of caregivers. This paper outlines a study protocol aimed at developing and evaluating the effectiveness of a general practice-based intervention to better meet the needs of caregivers of patients with advanced cancer. Methods/Design: Two hundred and sixty caregivers will be randomised into each of two arms of the intervention (520 participants in total) through patients with advanced cancer attending medical and radiation oncology outpatient clinics at two tertiary hospital sites. Consenting caregivers will be followed up for six months, and telephone surveyed at baseline, 1, 3 and 6 months following their entry into the study or until the patient's death, whichever occurs first. Assessment and management of the unmet needs of caregivers in the intervention arm will be facilitated through a specifically developed general practice-based strategy; caregivers in the control group will receive usual care. Qualitative interviews will be conducted with a sample of up to 20 caregivers and 10 GPs at the conclusion of their participation, to explore their views regarding the usefulness of the intervention. Discussion: This study will determine whether systematic assessment of caregiver needs supported by caregiver-specific information for General Practitioners is effective in alleviating the unmet needs experienced by caregivers caring for patients with advanced cancer.